A New Catalytic System with Balanced Activity and Durability toward Oxygen Reduction. Issue 19 (1st September 2020) - Cao, Zhenming; Xie, Minghao; Cheng, Haoyan; Chen, Ruhui; Lyu, Zhiheng; Xie, Zhaoxiong; Xia, Younan
Abstract: We report a new catalytic system by partially covering the uniform Pt nanocrystals on a carbon support with an ultrathin film derived from polyacrylonitrile (PAN). The use of Pt nanocrystals uniform in both size and shape effectively suppresses Ostwald repining, while partially covering them with a PAN‐derived film prevents migration, aggregation, and detachment from the support. In addition, the pyridinic N atoms on the edges of the thermally‐treated PAN film can also weaken the O=O bond, accelerating the reduction of oxygen. Upon optimization, the new catalyst exhibits a mass activity of 0.51 mA ⋅ μg −1 Pt toward oxygen reduction, substantially enhanced relative to the same catalyst without PAN (0.22 mA ⋅ μg −1 Pt ) and a commercial Pt/C (0.41 mA ⋅ μg −1 Pt ). The mass activity is essentially retained after 10, 000 cycles of accelerated durability test between 0.6 V and 1.1 V in oxygen‐saturated HClO4 . Even after aging in H3 PO4 at 220 °C for one week, the electrochemical surface area of the catalyst is still maintained. This catalytic system holds great promise for use in various types of fuel cells with a long lifetime. Abstract : Killing two birds with one stone : Partially covering the Pt nanocrystals on a carbon support with a PAN‐derived film greatly improves their catalytic durability while the pyridinic N atoms on the edges of the PAN film can accelerate oxygen reduction by weakening the O=O bond.